Technique to produce catalyst from egg shell and coconut waste for biodiesel production - Sulaiman, Sarina; Talha, Nur Syakirah (Springer Nature, 2018)
Many studies have been conducted to develop low cost catalysts to reduce the production cost. Several catalysts such as homogeneous/heterogeneous acid catalysts, homogeneous/heterogeneous base catalysts and biocatalysts (enzymes) have been studied and applied in the synthesis of biodiesel. Base- catalyzed transesterification is commonly used in commercial production because of high FAME yield in short reaction time and the reaction can be done in mild conditions as compared to acid-catalyzed transesterification. In the present study, egg shell and coconut waste were synthesized using calcination method at 800 °C for 4 h. SEM micrographs prove that the mixture of catalyst shows a bigger surface area. This result is expected to increase the yield of biodiesel. It can be concluded that biodiesel was produced successfully using palm oil and mixed catalysts.